Pengembangan Modul Pembelajaran Terintegrasi Keislaman Mata Kuliah Botani Tumbuhan Tinggi Materi Angiospermae Kelas Liliopsida - Dicka Debby Swastika (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
This study departs from field observations which state that the low student learning outcomes in 2013 that is with a percentage of 52.38% getting grades below the KKM, it needs the existence of more efficient teaching materials, to support student learning processes independently. This study aims to determine the validity, effectiveness and practicality of the Islamic integrated learning module in the High Plant Botany course for liliopsida class angiosperms material. This research uses the Research & Development method that was developed using the ADDIE model with stages: Analyze namely needs analysis, Design is the design / draft module, Development is product development / prototype based on design validation, design revision, small scale trial, revision I module, Implementation is the application of modules in large-scale trials of the control class / without modules, and the experimental class / using modules, Evaluation, namely revision II modules, final modules. The results of this study indicate that the module developed is feasible to be used in learning botanical lectures of tall plants obtained from the validity value of material experts 83.60% very good / valid, 80% good / valid design experts, 82% good / valid religious experts. The practicality of the use of modules obtained from observations of the implementation of learning by 91.41% was very successful and the student response questionnaire showed 99.15% of the practical modules used. The effectiveness of the application of the module is obtained from the increase in student learning outcomes with N-Gain of 0.77 in the high category compared to the control class of the value of N-Gain of 0.20 in the low category. Thus, the learning modules developed are valid, practical, and effective for use in learning.keyword: Modules, Integrated Islamic, Angiosperms, Liliopsida